Reproducibility of AJCC Criteria for Classifying Deeply Invasive Colon Cancers Is Suboptimal for Consistent Cancer Staging. (October 2020) - Panarelli, Nicole C.; Hammer, Suntrea T.G.; Lin, Jingmei; Gopal, Purva; Nalbantoglu, ILKe; Zhou, Lili; Cheng, Jerome; Gersten, Adam J.; McHugh, Jonathan B.; Parkash, Vinita; Lucas, Elena; Westerhoff, Maria
Abstract : The eighth edition of the American Joint Committee on Cancer (AJCC) Staging Manual attempts to address ambiguity in the pT category assignment for colon cancer from prior editions. Despite modifications, the distinction between the pT3 and pT4a categories continues to be a source of diagnostic confusion. In this study, we assessed interobserver agreement among pathologists from different institutions in the application of AJCC eighth edition criteria for categorizing deeply invasive colonic adenocarcinomas. We identified morphologic patterns that produce diagnostic confusion. We assessed 47 colon cancers that closely approached the serosal surface. Six pathologists with interest in gastrointestinal pathology and 4 focused in other subspecialties classified each case as pT3 or pT4a, based on examination of low-magnification and high-magnification images of the most deeply invasive area. Interobserver agreement was assessed using Fleiss' κ. Cases displayed 3 morphologic patterns at the advancing tumor edge, namely, (1) continuous invasion through an inflammatory focus, (2) pushing border, and (3) infiltrative glands and cell clusters with serosal reaction. Gastrointestinal pathologists achieved slight (κ=0.21) or moderate (κ=0.46) and (κ=0.51) agreement in each category, whereas agreement among nongastrointestinal pathologist was fair (0.31) and (0.39), or moderate (0.57) for each category, respectively. In 10 (21%) cases, the distinction between pT3 and pT4a would have changed the overall clinical stage. We conclude that histologic criteria for serosal penetration is a persistent source of diagnostic ambiguity for gastrointestinal and general pathologists in the pT categorization of colon cancers. Clarification of these criteria will help ensure uniform reporting of pathologic and clinical stage.